Impact of the works on the change in coastline of Tra Vinh province - Lan, Nguyen Thi Mong; Nguyen, Nguyen Hoang; Ly, Huynh mai; Tuan, Le Huu; Quyen, Vo Thi Hong (Vietnam Journal of Marine Science and Technology, 2019)
The coastline of Tra Vinh, about 65 km long from the mouth of Cung Hau to Dinh An, is composed of loose sediment, which is easily affected by natural factors and human activities. Based on satellite image analysis combined with survey and field measurements, the changes in coastline between 1966 and 2014 were identified. The results show that in this period the coastline had an average deposition rate of about 5–10 m/year. Dong Hai was the strongest deposition area with maximum rate of 40 m/year, average 28–30 m/year. The eroded coastline alternated with an average erosion rate of about 5–8 m/year. From 1990 up to now, many human constructions have been carried out along the coast of Tra Vinh, contributing to the impact of changing the shoreline. In the area of My Long Nam, Dong Hai and Long Vinh, the mangrove planting project was performed which helped to create continuous accretion of coastline with average rate of 17–33 m/year. In the period of 2009–2014, sea dykes in Hiep Thanh commune and Con Truong, Truong Long Hoa commune were built to prevent coastal erosion. During 2009–2014, Hiep Thanh coast and Truong Long Hoa coast were eroded at an average rate of 8–20 m/year and 6–10 m/year, respectively. After appearance of the dykes, the survey results show that in the 2014–2015 period, the shoreline of Hiep Thanh and Con Trung which has sea dykes was no longer eroded, but the adjacent coastline was more eroded at an average rate of 14–38 m/year. In Dan Thanh commune, where Duyen Hai electric center and Quan Chanh Bo canal were constructed, from 2009 to 2014, the coastline was eroded with the average rate of 12–24 m/year. In 2014–2015 period, coastal erosion was stronger at an average rate of 36–45 m/year.